Preparation of Activated Carbon-Based Solid Sulfonic Acid and Its Catalytic Performance in Biodiesel Preparation - Pi, Yuanzheng; Liu, Wenzhu; Wang, Jiani; Peng, Guanmin; Jiang, Dabo; Guo, Ruike; Yin, Dulin (Frontiers in Chemistry, 2022)
With activated carbon as raw material, AC-Ph-SO3H was prepared after oxidation with nitric acid, modification with halogenated benzene and sulfonation with concentrated sulfuric acid. After modified by 10% bromobenzene with toluene as a solvent for 5 h, followed sulfonation with concentrated sulfuric acid at 150 oC, the -SO3H content of prepared AC-Ph-SO3H was 0.64 mmol/g. Acid content test, infrared spectroscopy and Raman spectroscopy detection proved that the surface of AC-Ph-SO3H was successfully grafted with -SO3H group. When used as a catalyst for the methylation of palmitate acid, the catalytic performance of AC-Ph-SO3H was explored. When the reaction time was 6 h, the amount of catalyst acid accounted for 2.5 wt% of palmitic acid, and the molar ratio of methanol/palmitic acid was 40, the esterification rate of palmitic acid was 95.2% and the yield of methyl palmitate was 94.2%, which was much better than those of its precursors AC, AC-O and AC-Ph (both about 4.5%). AC-Ph-SO3H exhibited certain stability in the esterification reaction system and the conversion rate of palmitic acid was still above 80% after three reuses.